Rituals of death and dying in modern and ancient Greece : writing history from a female perspective. - Håland, Evy Johanne (Cambridge Scholars Publishing, 2014)
Multidisciplinary or post-disciplinary research is what is needed when dealing with such complex subjects as ritual behaviour. This research, therefore, combines ethnography with historical sources to examine the relationship between modern Greek death rituals and ancient written and visual sources on the subject of death and gender. The central theme of this work is women's role in connection with the cult of the dead in ancient and modern Greece. The research is based on studies in ancient history combined with the author's fieldwork and anthropological analysis of today's Mediterranean soci.